Gamification and Virtual Reality for Tongue Rehabilitation - Antonio Rodriguez; Miguel Chover; Imma Boada (IEEE Access, 2023)
Purpose: Lingual exercises based on tongue movements are common in speech therapy. These exercises can be tedious for patients, but gamification and virtual reality (VR) with head-mounted displays (HMD) can serve as effective strategies to enhance their motivation and engagement. However, the use of these technologies can be challenging for therapists due to a lack of technological skills. Material and Methods: A new system to support HMD-based VR for gamified tongue rehabilitation exercises is proposed. The system offers a variety of games that challenge users to achieve their goals through tongue movements and sound interaction. These games support different interaction actions that can be set by therapists using easy-to-use editors. The system also provide functionalities for patient follow-up. The system has been implemented and tested considering different technologies such as mobile devices, personal computers, and HMD complemented with an external camera to properly capture the tongue movements. Results: The therapists found the system to be user-friendly, requiring no additional support for effective utilization. The system’s versatility allows it to be used on mobile devices, as well as with augmented and virtual reality techniques, resulting in more engaging rehabilitation sessions. However, the sensibility of device movements to face detection strategies is a limiting factor of this configuration. In the case of using personal computers with HMD, better results are obtained and especially when virtual reality is considered. In this last case, it is better to consider illuminated scenarios to ensure the proper detection of facial movements. Conclusion: HMD-based VR for gamified tongue rehabilitation with ease to use editors to prepare sessions is a good strategy to improve patient engagement in tongue rehabilitation sessions.